Peranan Mahasiswa KKN 17 UINSU dalam Meningkatkan Mutu Desa Kelumpang Kampung, Kecamatan Hamparan Perak Kabupaten Deli Serdang Berbasis Agama, Pendidikan, Ekonomi, Teknologi, dan Kesehatan - Agustin Purba, Syahfina; Dary DN, Widia Ulan; Hidayah, Nur; Siahaan, Amiruddin (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This service article entitled "The Role of KKN 17 UINSU Students in Improving the Quality of Kelumpang Kampung Village, Hamparan Perak District, Deli Serdang Regency based on Religion, Education, Economics , Technology, and Healthy" discusses the role or involvement of students, especially the KKN 17 UINSU student group, which is carried out by 30 students from six faculties, namely the Faculty of Tarbiyah and Teacher Training, Faculty of Public Health, Faculty of Islamic Economics and Business, Faculty of Da'wah and Communication, Faculty of Science and Technology, Faculty of Sharia and Law. In carrying out this service the KKN 17 UINSU group implements 4 aspects namely Religion, Education, Economy, and Technology. This service activity was carried out for 30 days in Kelumpang Kampung Village, Hamparan Perak District, Deli Serdang Regency. In this journal article, scientific work uses qualitative research methods in the data collection process and research methods, namely by conducting field observations and describing activities or gruop 17 KKN programs that have been implemented in Kelumpang Kampung Village.